What causes changes in plant litter quality and quantity as consequence of grazing in the Patagonian Monte: Plant cover reduction or changes in species composition? - Campanella, María Victoria (2010)
In Patagonian Monte, as in other arid ecosystems, grazing has triggered changes in vegetation and soil such as plant cover reduction, changes in species composition and soil nutrient losses. Several mechanisms were proposed interconnecting these changes, but evidence supporting them is very scarce. On the basis of published data concerning plant cover by species along grazing gradients and leaf litter production of dominant species, we estimated the effects of grazing on a - quality (N, soluble phenolics and lignin concentrations) and b - quantity (leaf litterfall (LLF) and inputs of nitrogen, soluble phenolics and lignin to the soil) of leaf litter in the Patagonian Monte, discriminating the effect of plant cover reduction from that of species composition. We also evaluated the relationship between senesced leaves traits and the response of species to grazing (i.e. their relative change in plant cover). Grazing causes a reduction in LLF and in the inputs of nitrogen, soluble phenolics and lignin to the soil. In the case of LLF, this reduction was not only a result of the decrease in plant cover but also due to changes in species composition. In contrast, our results showed that the reduction in nitrogen, soluble phenolics and lignin inputs to the soil by LLF is only a consequence of plant cover reduction. Additionally, litter quality was affected through increasing concentration of N and secondary compounds (soluble phenolics and lignin). N and soluble phenolics concentration on senesced leaves were positively related to the response of species to grazing, suggesting that other factors instead of N are relevant to sheep foraging decisions.